2019
DOI: 10.1051/0004-6361/201834642
|View full text |Cite
|
Sign up to set email alerts
|

A physical approach to modelling large-scale galactic magnetic fields

Abstract: Context.A convenient representation of the structure of the large-scale galactic magnetic field is required for the interpretation of polarization data in the sub-mm and radio ranges, in both the Milky Way and external galaxies. Aims. We develop a simple and flexible approach to construct parametrised models of the large-scale magnetic field of the Milky Way and other disc galaxies, based on physically justifiable models of magnetic field structure. The resulting models are designed to be optimised against ava… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Improved Galactic magnetic field modelling is also necessary to verify these results. The IMAGINE consortium and the Bayseian inference code they are developing (Haverkorn et al 2019) aims to develop more sophisticated Galactic magnetic field modelling using dynamo models such as those in GALMAG (Shukurov et al 2019), which include higher-order dynamo modes and combinations of modes. The cross-correlation analysis presented in this work should be applied to an improved model for the Galactic magnetic field when such a model becomes available.…”
Section: Discussionmentioning
confidence: 99%
“…Improved Galactic magnetic field modelling is also necessary to verify these results. The IMAGINE consortium and the Bayseian inference code they are developing (Haverkorn et al 2019) aims to develop more sophisticated Galactic magnetic field modelling using dynamo models such as those in GALMAG (Shukurov et al 2019), which include higher-order dynamo modes and combinations of modes. The cross-correlation analysis presented in this work should be applied to an improved model for the Galactic magnetic field when such a model becomes available.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Stix (1975) showed that in a disk geometry a quadrupolar field should grow faster, while a dipolar field can arise as a result of asymmetries. Shukurov et al (2019) also presented a series of models where quadrupolar fields are favored in the disk, while dipolar geometries arise in the halo. In order to compare our findings to these analytical estimates, we need to split the magnetic field into a mean and a turbulent component.…”
Section: Mean and Turbulent Components Of The Magnetic Fieldmentioning
confidence: 99%
“…Elmegreen & Scalo 2004). Further, theoretical calculations can predict the structure of the magnetic field which turns out to be either dipolar or quadrupolar (Shukurov et al 2019), whereby the quadrupolar structures decay faster if the dynamo action is switched off. The field structure can then be determined by the symmetry of the magnetic field around the mid plane, where uneven symmetry determines a dipolar field while even symmetry indicates a quadrupolar field.…”
Section: Introductionmentioning
confidence: 99%